A Lagrangian perspective reveals the carbon and oxygen budget of an oceanic eddy - Alberto Baudena; Rémi Laxenaire; Camille Catalano; Artemis Ioannou; Edouard Leymarie; Marc Picheral; Antoine Poteau; Sabrina Speich; Lars Stemmann; Rainer Kiko (Communications Earth & Environment)
Abstract Quantifying the ocean’s ability to sequester atmospheric carbon is essential in a climate change context. Measurements of gravitational carbon export to the mesopelagic seldom balance the carbon demand or the oxygen consumption there, suggesting the potential presence of other mechanisms of carbon export. We deployed a biogeochemical Argo float in a cyclone in the Benguela upwelling system for five months, and estimated vertical carbon export and respiration in the eddy via particle imagery with an underwater vision profiler 6 in a quasi Lagrangian way. A sensitivity analysis shows that, under certain assumptions, oxygen consumption rates could match the carbon supply and carbon demand. We furthermore identified a mechanism of vertical particulate carbon export, the full eddy core submergence pump. Our analysis suggests that at 450 m depth, within this eddy, this pump exports about one fourth to half of the total carbon compared to the biological gravitational pump.